Capitalism [videorecording (DVD)] : a love story - Moore, Michael, 1954 April 23-; Moore, Michael, 1954 April 23-; Moore, Michael, 1954 April 23- (Anchor Bay Entertainment, 2010)
Filmmaker Moore examines the history of free-market capitalism in post-Reagan America and questions its efficacy as the basis for the nation's economy.